2007
DOI: 10.1016/j.aquaculture.2007.07.234
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive biology of the baby clam, Marcia opima, from two geographically separated areas of India

Abstract: A study of the reproductive cycle of the baby clam, Marcia opima (Gmelin) was conducted at two sites along the southeast (Tuticorin Bay) and southwest (Ashtamudi estuary) coast of India from December 1998 to January 2000. Histological evidence showed that baby clam from both the sites showed two spawning seasons. First spawning season was recorded from May to July in the southeast coast. In the southwest coast, the first spawning season was observed through March to May. A second spawning season from September… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…In C. farreri, the reproductive cycle is characterized by two phases: a short resting phase from November to December and gametogenesis during the rest of the year. Although the division of gonadal development is different in bivalves, the bases of these determinations are characteristics of gametogenesis and variations of oocyte diameters (Lango-Reynoso et al 2000;Darriba et al 2004;Drummond et al 2006;Li et al 2006;Suja and Muthiah 2007;Herrmann et al 2009). According to Liao et al (1983), the development of gonads in C. farreri were grouped into four stages (proliferative stage: JanuaryFebruary; growing stage: March-April; mature stage: May-July; resting stage: November-December) based on histological structure.…”
Section: Gametogenesismentioning
confidence: 99%
“…In C. farreri, the reproductive cycle is characterized by two phases: a short resting phase from November to December and gametogenesis during the rest of the year. Although the division of gonadal development is different in bivalves, the bases of these determinations are characteristics of gametogenesis and variations of oocyte diameters (Lango-Reynoso et al 2000;Darriba et al 2004;Drummond et al 2006;Li et al 2006;Suja and Muthiah 2007;Herrmann et al 2009). According to Liao et al (1983), the development of gonads in C. farreri were grouped into four stages (proliferative stage: JanuaryFebruary; growing stage: March-April; mature stage: May-July; resting stage: November-December) based on histological structure.…”
Section: Gametogenesismentioning
confidence: 99%
“…While on the other hand, female gonad showed significant alterations like decline of stroma and follicular rupture with further, arresting of oogonia, complete autolysis in oocytes and such alterations were observed particularly at low and high salinities and temperature ranges. A study by Suja and Muthiah [18] has observed significant effects of different temperatures on oocyte diameter. The observations revealed comparatively more decreased in oocyte diameter at 23 °C range than 28 °C.…”
Section: Discussionmentioning
confidence: 99%
“…In eastern Atlantic waters, the majority of spawning periods has been recorded in the summer months, May and June [ 16 ]. On the coast of India, the spawning season of Marcia optima has been recorded from May to July in the south-east, while in the south-west, it is from March to May [ 29 ].…”
Section: Discussionmentioning
confidence: 99%